Impact of Nonsurgical Periodontal Treatment on Blood Pressure: A Prospective Cohort Study - Lanau, Neus; Mareque-Bueno, Javier; Zabalza, Michel (European Journal of Dentistry, 2023)
Objectives Arterial hypertension and periodontitis are two of the most common diseases worldwide and recent evidence supports a causal relationship between them. Despite all antihypertensive strategies, an important number of patients are undiagnosed and a large number of the diagnosed fail to achieve optimal blood pressure (BP) measurements. Some studies point out that periodontal treatment could have positive effects on BP levels. The aim of this study is to determine if nonsurgical periodontal treatment can help BP level control in prehypertensive patients with periodontitis.Materials and Methods Thirty-five patients were included in the study and received nonsurgical periodontal treatment according to necessity. Clinical data, periodontal data, and BP measurements were taken at baseline, periodontal re-evaluation visit (4–6 weeks after treatment), and 6-month follow-up.Results Periodontal treatment caused a statistically significant reduction (p < 0.05) of systolic blood pressure (SBP) and diastolic blood pressure (DBP) at re-evaluation visit of 4.7 (p = 0.016) and 3.4 mm Hg (p = 0.015), respectively. The effect was maintained at 6-month follow-up visit with a reduction in SBP and DBP of 5.2 (p = 0.007) and 3.7 (p = 0.003) mm Hg, respectively.Conclusion Despite the limitations of this study, it suggests that nonsurgical periodontal treatment can be effective in lowering BP levels in patients with prehypertension and periodontitis. Moreover, it highlights the importance of dentists in prevention, detection, and control of this important cardiovascular risk factor.
Keywords: periodontitis; hypertension; prehypertension; blood pressure